Exosomes mediate LTB4 release during neutrophil chemotaxis. - Ritankar Majumdar; Aidin Tavakoli Tameh; Subhash B Arya; Carole A Parent (PLoS Biology)
Leukotriene B4 (LTB4) is secreted by chemotactic neutrophils, forming a secondary gradient that amplifies the reach of primary chemoattractants. This strategy increases the recruitment range for neutrophils and is important during inflammation. Here, we show that LTB4 and its synthesizing enzymes localize to intracellular multivesicular bodies, which, upon stimulation, release their content as exosomes. Purified exosomes can activate resting neutrophils and elicit chemotactic activity in an LTB4 receptor-dependent manner. Inhibition of exosome release leads to loss of directional motility with concomitant loss of LTB4 release. Our findings establish that the exosomal pool of LTB4 acts in an autocrine fashion to sensitize neutrophils towards the primary chemoattractant, and in a paracrine fashion to mediate the recruitment of neighboring neutrophils in trans. We envision that this mechanism is used by other signals to foster communication between cells in harsh extracellular environments.